Survei Sarana dan Prasarana Pendidikan Jasmani SMK di Kabupaten Banjarnegara Tahun - amelia, lisa; Nurharsono, Tri (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study is to find out that the facilities and infrastructure owned by each Vocational School in the Regency are in accordance with the established standards. This study uses a descriptive percentage approach with the research location in SMK in Banjarnegara Regency. With a sample of 2 private vocational schools and 6 state vocational schools. Collecting data using survey methods with interview, observation and documentation techniques, while the data analysis technique used is descriptive.The results of the research are as follows: in general the sports facilities and infrastructure of Vocational Schools in Banjarnegara Regency, on average are classified in the Good Enough category to support the learning process of Physical Sport education ideally.The conclusion in this study is that the physical education facilities and infrastructure of Vocational Schools in Banjarnegara Regency are said to be in the Good category for volleyball, basketball football and for athletics they are categorized as adequate because equipment such as bullets, javelin, discs are still plentiful in terms of number, and for swimming and gymnastics, they are in the less category where from 8 schools are still very lacking in facilities and infrastructure.